Realizing high performance flexible supercapacitors by electrode modification. Issue 62 (7th December 2021) - Xia, Tong; Zhao, Depeng; Xia, Qing; Umar, Ahmad; Wu, Xiang
Abstract : We prepare hybrid structured NiCo2 S4 @PPy nanoarchitectures by a hydrothermal method and subsequent electrodeposition process. The assembled asymmetric device presents an energy density of 59.59 W h kg −1 at 1404.04 W kg −1 . Abstract : It is well known that the structure of an electrode material seriously affects its electrochemical performance. In this study, we prepare hybrid structured NiCo2 S4 @PPy nanoarchitectures by a hydrothermal method and subsequent electrodeposition process. The specific capacitance of the obtained sample is 1733.23 C g −1 at 1 A g −1 . The assembled asymmetric device presents an energy density of 59.59 W h kg −1 at 1404.04 W kg −1 . The excellent electrochemical performance can be attributed to the synergistic effect between the high theoretical specific capacitance of the NiCo2 S4 sheets and the superior cycling stability of the PPy film. The device also shows an outstanding mechanical flexibility at different bending angles.